Two autotrophic processes drive palnt esablishment in a polar desert - D. Daffonchio; S. Borin; F. Tambone; F. Mapelli; S. Ventura; F. Schubotz (2010)
Some key processes in land reclamation in hot and cold deserts are yet poorly understood despite a challenge for the future is to limit the actual ongoing desertification in many regions of the planet. Moraines refer to any glacially-formed accumulation of unconsolidated rock debris that occur in currently or formerly glaciated regions. The ongoing global warming is causing glacier retreat and exposes the formerly ice-covered rock debris to the atmosphere. Hence, moraines are ideal environments for studying the driving mechanisms of soil formation and plant colonization processes. Polar moraines above the 75°N are classified as cold deserts since for most of the year, water is immobilized as ice and precipitations is very sparse. At these sites, formation of soil and plant biocenosis on the substrate recently released from permanent ice cover is slow and hampered by the harsh environmental conditions (low water availability and low temperature) and by nutrient paucity that limits microbial primary production, the formation of organic matter and plant establishment. In polar moraines photosynthesis by cyanobacteria and microbial heterotrophic assimilation of organic materials released by animals or transported by wind are commonly considered the processes initiating soil formation and mediating plant colonization. Here we report an alternative autotrophic mechanism initiating soil formation. In the glacier foreland of Midtre Lovenbreen glacier (78°56’N) in Ny Alesund, Svalbard, the chemolithoautotrophic iron-sulfur oxidation of pyrite triggers early soil formation and promotes primary colonization by plants. Rock pyrite weathering mediated by Acidithiobacillus ferrooxidans determines acidity and corresponding fertility gradients, where water retention, cation exchange capacity and nutrient availability are increased. A new, previously unrecognized soil genesis and crop formation model, with potential past and present, terrestrial and extraterrestrial analogues has been dissected by using a interdisciplinary ...